2011
DOI: 10.1002/cncr.25874
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric oxygen treatment improved neurophysiologic performance in brain tumor patients after neurosurgery and radiotherapy

Abstract: BACKGROUND:Cognitive performance often is impaired permanently in long-term brain tumor survivors after neurosurgery and radiotherapy. Hyperbaric oxygen treatment (HBOT) stimulates neovascularization of hypoperfused tissue and may result in improved functionality of damaged tissue. In this pilot study, clinical neurophysiologic tests were used to assess the effect of HBOT on brain performance. METHODS: Ten long-term brain tumor survivors received HBOT for severe cognitive deficits after neurosurgery and radios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 29 publications
(41 reference statements)
1
18
0
Order By: Relevance
“…Recent reports have largely demonstrated that HBO and NBO have positive influences on cognitive abilities, such as memory, visuospatial and verbal abilities, addition (related to working memory function) and n-back tasks (Chung et al 2009, Choi et al 2010, Schellart et al 2011. Our findings suggest that these reported neuro-psychological improvements might be associated during HBO exposure to rCBF distribution changes found in the regions encompassed in the DAS.…”
Section: Discussionsupporting
confidence: 53%
“…Recent reports have largely demonstrated that HBO and NBO have positive influences on cognitive abilities, such as memory, visuospatial and verbal abilities, addition (related to working memory function) and n-back tasks (Chung et al 2009, Choi et al 2010, Schellart et al 2011. Our findings suggest that these reported neuro-psychological improvements might be associated during HBO exposure to rCBF distribution changes found in the regions encompassed in the DAS.…”
Section: Discussionsupporting
confidence: 53%
“…It has been reported that the course of brain tumors is related to the efficacy of HBO therapy. Early use of HBO has important implications for the reduction of inflammatory factors, improvement of hypoxic symptoms, recovery of nerve function and brain function (23). In this study, cerebral arterial flow velocity in the observation group after treatment (96.74±20.86 cm/sec) was significantly lower than that in the control group (119.52±18.27 cm/sec; P<0.001).…”
Section: Discussionmentioning
confidence: 99%
“…16,45 studies did not include a comparator group. In nine of the 21 nonpharmacological intervention studies, preexisting subjective or objective cognitive impairment was a criterion for inclusion in the study [13][14][15]18,20,37,39,40,44 ; hence, these studies evaluated cognitive deficit amelioration (as opposed to prevention). The sample sizes of the nonpharmacological studies included in this review ranged from 3 44 to 143.…”
Section: Nonpharmacological Studiesmentioning
confidence: 99%
“…45 Five of the 21 studies were multicentre, 12,19,21,38,42 and the remainder were single-centre studies. 11,[13][14][15][16][17][18]20,22,37,[39][40][41][43][44][45] Like the pharmacological intervention studies, the mean/median age of participants in the nonpharmacological intervention studies was similar, in the fifth and sixth decades of life, although participant ages were not reported in one study. 11 Gender of participants was not reported in two of the studies, 11,21 but where it was, there was reasonable gender balance in most studies.…”
Section: Nonpharmacological Studiesmentioning
confidence: 99%
See 1 more Smart Citation